Factors affecting accounts receivable in parcel companies In Nairobi county - Onyango, Elly Odhiambo (My University, 2012)
The study evaluated factors affecting accounts receivable of parcel companies in Nairobi County. Accounts receivable as an important component of corporate liquid assets is critical to the operation of parcel delivery companies. Most parcel companies in Nairobi County observed hardly manage their short-term financial obligations due to their poor management of accounts receivable. The study sought to determine the factors affecting accounts receivable in parcel companies in Nairobi County and specifically to determine the effects of credit management policies on accounts receivable in parcel companies in Nairobi County, to find out the extent to which credit management skills affect accounts receivable in parcel companies in Nairobi County, to find out the extent to which competition affects accounts receivable in parcel companies in Nairobi County and to determine the effects of credit management information system on accounts receivable of parcel companies in Nairobi County. The study used descriptive research incorporating survey design. The target population consisted of senior officials of companies offering parcel services in Nairobi County. A population of eighty seven (87) licensed operators of parcel companies was surveyed. Data was collected by use of questionnaires delivered by courier service and electronic mails to various respondents. The questionnaire included a likert scale, open ended questions as well as quantitative data which was analyzed by use of MS Excel and summarized using descriptive statistics in the form of tables, frequencies and percentages. Textual data was analyzed qualitatively. The major findings developed from this study were that parcel companies in Nairobi County are not efficient in credit management. The study also found out that parcel companies are not efficient on the use of credit management policies. Further, the study established that parcel companies in Nairobi County inefficiently undertake skills analysis before granting any credit management job. Thirdly, the study established that competition is a critical factor affecting whether the companies offer services in cash or credit resulting into accounts receivable.Finally,it was established that most companies still use general accounting applications that do not have adequate capabilities to give proper credit information. The study recommended that there is need for parcel companies in Nairobi County to undertake continuous benchmarking of their accounts receivable management strategies and policies with other players in the industry. Credit management skills are important in lifting the abilities of credit officers to leverage credit into strategic position and greater profitability. The current competitive environment, parcel companies will triumph only if they are able to offer credit to clients with right credit strategies. Parcel companies need to put effective credit management information system that supports accounts receivable management and provides accurate information on clients to be used in analysis and offering of credit to customers.